The Impact of Social Environment on the Sexual Self-Regulation of University Students in Uganda - Musa Muwaga; Fuad Nashori; Achmad Sholeh (Universitas Muhammadiyah Yogyakarta, 2020)
Most societies consider sexual self-regulation to represent a general temptation control mechanism, postponing gratification. This study aims to determine the social environment's impact on university students' sexual self-regulation in Uganda. The data were obtained using convenience technique sampling of undergraduate students at university